A review on optimization of V2V charging services in intelligent transportation environment - ZHANG Keyang; LIU Shuohan; CAO Yue; LIN Hai; KANG Jiawen; AI Haojun (物联网学报, 2025)
In recent years, the electric vehicle (EV) industry has seen vigorous growth. However, deficiencies in charging infrastructure layout, structure and operation have become obstacles to further market expansion. Thus, relevant policies have listed the Internet of vehicles (IoV), vehicle-grid bidirectional interaction, distributed energy storage, and other charging facilities alongside cutting-edge technological innovations in the smart energy sector as key development priorities. Since traditional grid to vehicle (G2V) charging model struggles to meet the large-scale parallel charging demands of EVs under limited charging infrastructure conditions, the existing structure of energy consumption needs to adapt to the dynamic changes in demand. Against this backdrop, the concept of vehicle to vehicle (V2V) charging has been proposed to alleviate the limitations of G2V charging mode in terms of time and space domains, exploiting the potential of smart EVs as mobile distributed energy storage units. This facilitates flexible energy supply, offering a new approach to optimizing EV charging services and supporting the development of future intelligent transportation system (ITS). Focusing on the optimization direction centered around V2V charging, the relevant researches in recent years were reviewed. Firstly, the charging services in the intelligent transportation scenarios were classified, and an overview of the V2V charging mode was provided. Then, the proposed V2V charging management schemes from a technical emphasis perspective were categorized, and the optimization strategies were elaborated in detail. Finally, the development prospects of V2V charging in ITS were exlored, and open research topics for future studies were discussed.